24.2: Real‐Time Rendering 360° Floating Light‐Field 3D Display. Issue 1 (June 2015) - Su, Chen; Zhong, Qing; Xu, Liang; Li, Haifeng; Liu, Xu
Abstract : With light field reconstruction technique, real‐time rendering a floating colorful three‐dimensional scene in the air is implemented. The high‐frame‐rate projector, rotating transmitted directional diffuser and high‐speed data processing and transmission module are utilized to create the light field of animated 3D scenes with higher light use efficiency.